Magnetic nanocellulose from Cyperus rotundas grass in the absorptive removal of rare earth element cerium (III): Toxicity studies and interpretation. (January 2022) - Shahnaz, Tasrin; Vishnu Priyan, V.; Jayakumar, Anjali; Narayanasamy, Selvaraju
Abstract: In this study a very common grass named Cyperus rotundas was used to extract cellulose which was converted to magnetic grass nano cellulose (MGNC) to adsorb rare earth element Cerium (Ce (III)). The prepared MGNC was analyzed with sophisticated technique to determine the alteration in physical and chemical properties before and after adsorption with the pollutant Cerium. Parameters like pH, temperature, MGNC dosage and initial concentration of Ce were optimized to check parameters influencing the adsorption of Ce (III). The optimized experimental data were perfectly modelled into Langmuir model with adsorption capacity of 353.04 mg g −1 for Ce (III). For kinetics the data fitted into pseudo second order model. To check the efficacy of MGNC in real scenario, untreated and treated Ce was used for phototoxicity studies with 4 different plant seeds. Apart from this, model fish, Danio rerio was used to check the toxicity level on aquatic organism before and after adsorption of Ce (III) with MGNC. This study showed the efficient use of MGNC and maximum removal of Cerium from wastewater and the magnetic behavior incorporated adds advantage of easy retrieval. Graphical abstract: Image 1 Highlights: Nanocellulose was prepared from cellulose extracted from Cyperus rotundas grass. Isotherm, kinetics and thermodynamics were checked after treating Ce (III) on MGNC. MGNC gave maximum adsorption efficiency of 353.04 mg/g for Ce (III). Seed and aquatic model organisms were used to perform ecotoxicological assessment.